Remission with an intervention: is metabolic surgery the ultimate solution? - Hanipah, Zubaidah Nor; Rubino, Francesco; Schauer, Philip R. (W.B. Saunders, 2023)
Long-term remission of type 2 diabetes following lifestyle intervention or pharmacotherapy, even in patients with mild disease, is rare. Long-term remission following metabolic surgery however, is common and occurs in 23% to 98% depending on disease severity and type of surgery. Remission after surgery is associated with excellent glycemic control without reliance on pharmacotherapy, improvements in quality of life, and major reductions in microvascular and macrovascular complications. For patients with type 2 diabetes, early intervention with metabolic surgery, when beta cell function still remains intact, provides the greatest probability of long-term remission as high as 90% or more.